2022
DOI: 10.3389/fpubh.2022.907732
|View full text |Cite
|
Sign up to set email alerts
|

Global Experiences of Community Responses to COVID-19: A Systematic Literature Review

Abstract: ObjectiveThis study aimed to conduct a systematic review of the global experiences of community responses to the COVID-19 epidemic.MethodFive electronic databases (PubMed, Embase, CINAHL, ScienceDirect, and Web of Science) were searched for peer-reviewed articles published in English, from inception to October 10, 2021. Two reviewers independently reviewed titles, abstracts, and full texts. A systematic review (with a scientific strategy for literature search and selection in the electronic databases applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…A study has shown that medical staff can prevent iatrogenic infections by taking herbal decoctions and moxibustion based on TCM principles in the hospital [ 43 ]. Prevention methods of ICWM have been widely used in community prevention, home isolation, and other situations, thus reducing the risk of transmission and protecting public health [ [44] , [45] , [46] ]. With the development of the global epidemic and the increase of discharged patients, the integration of traditional Chinese and Western medicine to prevent and control COVID-19 and the treatment of the recovery period will be the focus of future research.…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that medical staff can prevent iatrogenic infections by taking herbal decoctions and moxibustion based on TCM principles in the hospital [ 43 ]. Prevention methods of ICWM have been widely used in community prevention, home isolation, and other situations, thus reducing the risk of transmission and protecting public health [ [44] , [45] , [46] ]. With the development of the global epidemic and the increase of discharged patients, the integration of traditional Chinese and Western medicine to prevent and control COVID-19 and the treatment of the recovery period will be the focus of future research.…”
Section: Discussionmentioning
confidence: 99%
“…This can ensure that communities can access accurate and up-to-date information and respond effectively to emergencies. However, it is important to note that even in emergencies, striving for effective two-way communication where possible [ 26 , 27 ]. This helps ensure that communities better understand their risks and can participate in response and recovery efforts [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%